2017
DOI: 10.1080/01443615.2016.1250734
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinase-9 and its substrate level in patients with premature rupture of membranes

Abstract: In this study, 30 case of patients with full-term premature membrane rupture and another 30 cases of full-term delivered subject without premature rupture of membranes (PROM) were selected to explore the relationship between premature membrane rupture with matrix metalloproteinase 9 (MMP-9) and its substrate level. Results showed the plasma zinc, MMP-9 in serum and amniotic fluid increased in patients with PROM; their type IV collagen in serum and foetal membrane decreased. Increased Zinc ion concentration res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In case of hypertension during pregnancy, there is reduced uteroplacental perfusion as a result of abnormal cytotrophoblast invasion of spiral arterioles and endothelial dysfunction and in turn placental ischemia which brings premature rupture of membrane [31, 32]. This premature rupture of membranes in pregnant women can be happen due to type IV collagen reduction in serum and fetal membrane by Matrix Metalloproteinase-9 [33], and increased cytokine concentrations that may contribute to the endothelial damage [34].…”
Section: Discussionmentioning
confidence: 99%
“…In case of hypertension during pregnancy, there is reduced uteroplacental perfusion as a result of abnormal cytotrophoblast invasion of spiral arterioles and endothelial dysfunction and in turn placental ischemia which brings premature rupture of membrane [31, 32]. This premature rupture of membranes in pregnant women can be happen due to type IV collagen reduction in serum and fetal membrane by Matrix Metalloproteinase-9 [33], and increased cytokine concentrations that may contribute to the endothelial damage [34].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-4535 and miR-1915-5p in the amniotic fluid was found to be related to the fetal and maternal inflammatory responses. Intense inflammatory responses are mediated by various cytokines or inflammatory products, including IL-1β, TNF-α, IL-6, PAF, IFN-γ, PGE2, MMP-1 and MMP-2 [19]. In particular, the fetal inflammatory response syndrome is characterized by systemic future science group 10.2144/fsoa-2021-0006 inflammation and elevated fetal plasma IL-6 levels [62].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, among the infection of miCAM (U. parvum, S. agalactiae, G. vaginalis, S. sanguinegens, P. bivia, L. jensenii and M. hominis), we have previously reported that 33 of 43 (77%) patients with severe chorioamnionitis were identified as having U. parvum in amniotic fluid, using a next-generation sequencing method [13]. In contrast, inflammatory changes have a greater association with adverse perinatal outcomes than the presence of the aforementioned microorganisms [18][19][20][21], thus promising predictive biomarkers for chorioamnionitis must be identified in host inflammatory reactions and via absolute quantification and sequencing of 16S rDNA.…”
mentioning
confidence: 99%
“…Over expression of matrix metallopeptidase-9 (MMP-9) causing degradation of the extracellular matrix within the amniotic membrane has been suggested as a possible mechanism. 39,40 MMP-9 has also been implicated as part of the pro-inflammatory milieu and serum MMP-9 is indeed elevated in AD patients. 41 No other obstetric outcomes were clearly associated with maternal AD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association did not meet statistical significance in sub‐analysis. Over expression of matrix metallopeptidase‐9 (MMP‐9) causing degradation of the extracellular matrix within the amniotic membrane has been suggested as a possible mechanism . MMP‐9 has also been implicated as part of the pro‐inflammatory milieu and serum MMP‐9 is indeed elevated in AD patients .…”
Section: Discussionmentioning
confidence: 99%